Modified Bacterial Cellulose-Based Composite Profile for Drug Release of Tetracycline Hydrochloride - Cahyani, Ni Wayan Chyntia Pramesti; Yuanita, Emmy; Dharmayani, Ni Komang Tri; Sudirman, Sudirman; Sudewianingsih, Ni Made; Ulfa, Maria (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Bacterial cellulose (BC) is a biodegradable natural polymer with high mechanical strength and non-toxicity. This biopolymer is widely used as a candidate in biomedical fields, such as drug delivery, wound healing, and filtration systems. However, BC lacks antibacterial activity which limits its use in biomedical applications. So, modification of BC-based composite is required. This study aims to examine the effects of modifying BC-based composites with fillers such as graphite (G) and polyvinyl alcohol (PVA) on the release of tetracycline hydrochloride (TCH) drugs. Adding fillers to BC can alter its physical and mechanical properties, reducing its porosity and swelling rate in acidic and alkaline mediums. The drug release of TCH from modified BC-based composites follows the Korsmeyer-Peppas and Hixson-Crowell kinetics models. Adding filler and TCH antibiotic to the composite enhances its antibacterial activity against Staphylococcus aureus with a significant inhibition zone. The results of the inhibition zone show that composites have the potential to be applied in biomedical fields, especially in transdermal patches.